2013
DOI: 10.12816/0001540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Red-Green Color Vision Defects among Various Ethnic Groups of Students in Erbil City

Abstract: The incidence of color blindness varies from race to race and in different geographical area. Since, there is no such report about the prevalence of color blindness in the Kurdistan region (North of Iraq), the present study had been conducted to find out the incidence of color blindness among preliminary, secondary and college students of Erbil city, Kurdistan region-Iraq. Participant's (n=1856, 1275 males, 581 females, age group 7 to 25 years) color vision was tested by using Ishihara chart. Among 1275 male s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 18 publications
2
25
2
Order By: Relevance
“…Thus, all reds, greens, oranges, browns, purples, blues and grays will be impossible to identify precisely [11]. This study revealed that prevalence of CVD among male students was (6.36), Three previous studies from Iraq showed results near to this study result , prevalence rate among the students of Erbil City of (8.47) , among adults in Baghdad (6.75), and (8.19) among children from Basrah province [8,12,13]. Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14].…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Thus, all reds, greens, oranges, browns, purples, blues and grays will be impossible to identify precisely [11]. This study revealed that prevalence of CVD among male students was (6.36), Three previous studies from Iraq showed results near to this study result , prevalence rate among the students of Erbil City of (8.47) , among adults in Baghdad (6.75), and (8.19) among children from Basrah province [8,12,13]. Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14].…”
Section: Discussionmentioning
confidence: 47%
“…In large study in India, researchers found that 7.95% deutans and 3.22% protans [26], In Jordan, 12 of cases of deutan and 7 cases of protans [15], In Nepal , 16 cases out of 19 cases of deutan types [27] , In study done in Philippine , (78.95%)of cases of CVD of deutan types [28]. In Erbil, cases of deutans are slightly more than cases of protans [8].while a Turkish study has reported about 5.10% protans and 2.23% deutans among male [29]. Because, the CVD is inherited the condition, its allocation is likely to be changeable among ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Internationally reported overall CVD differs in different races and geographical areas. 7,10 Health care workers with color deficiencies experience difficulties in identifying changes in body color such as pallor, cyanosis, jaundice and erythema.…”
Section: 7mentioning
confidence: 99%